A Survey on the Role of Principals in Teacher Promotion in the Philippines - Simbre, Abegail; Aquino, John Michael; Palad, Ingrid (Thai Journal of East Asian Studies, 2023)
This study surveyed the roles of principals in teacher promotion, challenges and initiatives based on Domain 4 of Philippine Professional Standards for School Heads (PPSSH) and Domain 7 of Philippine Professional Standards for Teachers (PPST). Qualitative research was done with data gathered by focus group discussion with six experienced teachers and interviews with four principals in Philippine public schools. An online meeting platform was used for in-depth discussion of roles, concerns and challenges pertaining to promotion. Results were that principals consistently fulfilled most of their roles stated in PPSSH: personal and professional development; professional reflection; performance management; professional development of school personnel; leadership and development in individuals and teams; general welfare of human resources; and rewards and recognition, except for the professional networks strand. Both teacher and principal participants agree that principals serve as effective models for teachers, with a positive attitude about work, providing technical assistance and opportunities for teachers to assume relevant tasks, according recognition, developing soft skills of teachers, pursuing further study, and self-initiative as promotion requirements. These findings suggest that a career advancement system should include three key competencies: functional, core behavioral, and professionalism and ethics. These should continuously and systematically address concerns of teachers about promotion and better meet organizational needs.